Modeling the Quality of Current Collection Under the Conditions of a Growing Speed of Rolling Stock - Kaniewski, M.; Kuznetsov, Valeriy; Hubskyi, Peter V.; Sychenko, Viktor G.; Antonov, Andrii V. (Kaunas University of Technology, 2020)
EN: The use of high-speed electric rolling stock necessitates increased requirements for the reliability of its operation. Particular attention should be paid to the interaction of the contact line with current collectors. An important area is the development of tools for modeling the interaction of catenary with current collectors. At present, in some sections of railways, there is a need to increase the speed of trains and adapt the requirements for the design of the contact lines, which allow to the owner of the infrastructure to achieve the correct parameters for dynamic interaction on the pantograph-contact line interface in the point of view of the requirements of Energy TSI. In this work the authors discussed the problem of the equivalenting the contact line during the simulation
V. Sychenko: ORCID 0000-0002-9533-2897; A. Antonov: ORCID 0000-0001-5701-6087
Keywords: catenary; interaction; pantograph; simulation; equivalenting; КІСЕ